PATTERNS OF JAPAN SEISMICITY BEFORE THE LARGE EARTHQUAKES OF 1985-1988 - Malyshev A.I.; Tikhonov I.N. (My University, 1996)
A catalog of Japanese earthquakes was used to find some empirical patterns of seismicity before large (M ≥ 6.0) earthquakes in the region. These patterns were identified by the numerical modeling of sequences of seismic events using the differential equation of self excited processes. The origin times of main shocks emerging from the equation were investigated for stability. It is shown that the precursory area of an M ~7.5 earthquake involves the entire region. Fourteen seismic sequences preceding M ~6.0 earthquakes were studied. The time of a large seismic event was predicted to within a day in eight cases and within 2.4 days in six cases. The average decision advance time was 21.1 days before the event.